Peningkatan Kapasitas SDM Pengelola Bumdes Desa Cibodas Kabupaten Bandung Barat - Marlina, Reni; Suwandi, Yudi (Jurnal Dharma Bhakti Ekuitas, 2024)
BUMDes Karya Mandiri Lembang District in West Bandung Regency is one of the 165 BUMDes in the West Bandung Regency area engaged in the business of providing clean water, stall/kiosk rental, multi-purpose buildings and agribusiness. The problems experienced by BUMDes Karya Mandiri are that BUMDes are not yet optimal as drivers of the village economy, weak managerial capabilities of BUMDes management resources and limited capital. Based on this, service is carried out in the form of training for BUMDes managers and staff and assistance related to Human Resources aspects and institutional aspects related to improving the managerial abilities of BUMDes managers and socializing alternative funding using digital information technology. The results of the activity are an increase in the human resource capacity of BUMDes managers and an increase in financial literacy regarding alternative sources of external funding which can increase the understanding of BUMDes managers in applying management principles in managing BUMDes as well as increasing the financial literacy of BUMDes managers so that they can improve performance in carrying out the operationalization of BUMDes. Keywords: BUMDes, Managerial Capabilities, Human Resources, Funding Abstrak BUMDes Karya Mandiri Kecamatan Lembang di Kabupaten Bandung Barat merupakan salah satu BUMDes dari 165 BUMDes di kawasan Kabupaten Bandung Barat bergerak dibidang usaha penyelenggaraan air bersih, penyewaan warung/kios, Gedung serba guna dan agribisnis. Permasalahan yang dialami oleh BUMDes Karya Mandiri adalah belum optimalnya BUMDes sebagai penggerak ekonomi desa, lemahnya kemampuan manajerial sumber daya pengelola BUMDes dan keterbatasan permodalan. Berdasarkan hal tersebut maka dilakukan pengabdian dalam bentuk pelatihan kepada pengelola dan staf BUMDes dan pendampingan terkait aspek Sumber Daya Manusia dan aspek kelembagaan berkaitan dengan peningkatan kemampuan manajerial dari pengelola BUMDes dan sosialisasi mengenai alternatif pendanaan dengan pemanfaatan teknologi informasi digital. Hasil dari kegiatan yaitu adanya peningkatan kapasitas SDM pengelola BUMDes dan peningkatan literasi keuangan mengenai sumber alternatif pendanaan eksternal dapat meningkatkan pemahaman pengelola BUMDes dalam menerapkan prinsip manajemen dalam pengelolaan BUMDes serta peningkatan literasi keuangan pengelola BUMDes sehingga dapat meningkatkan performansi dalam menjalankan operasionalisasi BUMDes Kata kunci: BUMDes, Kemampuan Manajerial, Sumber Daya Manusia, Pendanaan